Preventing violence and promoting healthy intimate relationships: Interventional analysis with adolescents (Research, Society and Development, 2021)
Objective: to evaluate the impact of a multicomponent intervention program to raise awareness among adolescents about violence in intimate relationships, enabling them to build healthy relationships. Method: Quasi-experimental study with students from the 8th and 9th grade of elementary school in a public school before (n = 105), after (n = 88) and after six months (n = 82) of an intervention based on the ecological model. The diagnostic instruments were the sociodemographic questionnaire; knowledge about violence in intimate relationships; and social skills. Descriptive and inferential statistics were used, using the chi-square and Wilcoxon tests. Results: The average age was 13.9 years; 48.6% of female adolescents; 75.2% have already had some type of intimate relationship, where 6.7% recognized themselves as victims and / or perpetrators of some type of violence. The groups did not present significant differences in the comparison of the collection times. Conclusion: It is concluded that programs like this still need further practical study, considering diagnostic tools and strategies selected for interventions that are better suited to the needs of the participants to be reached. The importance of disseminating ineffective experiences is emphasized, since negative results can contribute to reformulation and improvement for future uses.